Green roof influence over the characteristics of the linear thermal bridges. (August 2019) - Baciu, I-R; Isopescu, D N; Taranu, N; Maxineasa, S G
Abstract: Urban heat island (UHI) significantly affects the thermal-energy performance of the buildings. Moreover, urban materials absorb solar and infrared radiation, heat accumulation is dispersed in the atmosphere, a fact which increases air temperature. In this context, green roofs are the most suitable solution to resolve these vital issues. The expanding benefits of a green roof, such as energy saving, thermal insulation, and mitigating heat island effect emphasize the key role of this structure in overall thermal performance of buildings and microclimate conditions of indoor spaces. The main objective of the study is to analyse the influence of extensive green roof on the heat flow, in the thermal bridges developed structurally in buildings where they might replace the classical terrace roof. The influence is analysed through the comparison of the thermal impact of a classical terrace roof and that of an extensive green roof, through thermal characteristics of their components. The first part of the paper presents the structures of each type of roof and their thermic characteristics established and evaluated according to the normative regulation in force. In this context, the classical terrace roof and extensive green roof are examined from a thermic point of view, analysing the parameters of the types of thermal bridges usually met, in order to establish if the extensive green roof might have an influence on the overall heat flow. In conclusion, the unpredictable results obtained for the analysed thermal parameters let conclude that the extensive green roof solution presents a favourable environmental impact, promoting a "beautiful" added value to a building, in terms of both sustainability and aesthetics.